2009
DOI: 10.1016/j.jcws.2009.09.001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Sustained Antimicrobial Activity of a New Silver Alginate Dressing

Abstract: Silver-containing dressings are considered fundamental to the management of infected acute and chronic wounds, specifically burns. The aim of this study was to determine both the spectrum of activity and efficacy of an Alginate/CMC Silver Dressing (ACSP) on planktonic microorganisms by conducting a 21-day repeat-challenge log reduction study. ACSP was found to have a microbiocidal effect, for up to 21 days, on all bacteria and yeast challenged. The results demonstrated an antimicrobial efficacy similar to Hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…Silver alginate wound dressings have demonstrated beneficial effects on wound healing, based principally on the physical properties of the dressing (29). In particular, silver alginate wound dressings have been shown to have the ability to ‘modulate’ wound exudates levels and maintain a ‘therapeutic’ level of antimicrobial activity at the wound dressing interface and within the wound dressing itself (30). In addition, silver alginate wound dressings have clinically been shown to prevent wound infections (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver alginate wound dressings have demonstrated beneficial effects on wound healing, based principally on the physical properties of the dressing (29). In particular, silver alginate wound dressings have been shown to have the ability to ‘modulate’ wound exudates levels and maintain a ‘therapeutic’ level of antimicrobial activity at the wound dressing interface and within the wound dressing itself (30). In addition, silver alginate wound dressings have clinically been shown to prevent wound infections (12).…”
Section: Discussionmentioning
confidence: 99%
“…In conjunction with previous studies (12,29, 30), our aim was to enhance our knowledge of the antimicrobial activity of a silver alginate dressing further by investigating its broad spectrum of activity on both planktonic and sessile microorganisms. It was our hypothesis that a silver alginate dressing would remain efficacious independent of selected cell wall composition (Gram positive and Gram negative), antibiotic‐resistance category and biofilm phenotype on microorganisms commonly recovered from wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Silver alginate wound dressings are routinely used in the management of infected wounds, or those wounds considered being at risk of infection as they are known to have antimicrobial activity against a broad range of wound microorganisms, 25 even at different pH values 26 . In a recent in vitro comparative study of a silver alginate and a silver carboxymethyl cellulose dressing, conducted by Bradford et al, 27 it was showed that a silver alginate dressing maintained ionic silver levels at a high enough level that could be sustained for up to 21 days. Unfortunately, sustained antimicrobial efficacy over this time period was not shown for the silver carboxymethyl cellulose dressing on a number of wound isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a loss of antimicrobial efficacy may be anticipated as the silver concentration reduces in the dressing over time, because of the demands of the microbial bioburden. This is important in situations where wound dressings may be in place for several days, with silver alginate dressings recently being shown to demonstrate efficacy for up to 21 days (24). For this reason, to examine the antimicrobial persistence of the test dressing, the CZOI assay was designed to monitor performance over time, up to 13 days, until the antimicrobial effect was no longer apparent.…”
Section: Discussionmentioning
confidence: 99%
“…The use of silver dressings has widely been promoted as a means of reducing the bioburden of wounds without concomitant development of resistant bacterial strains (22) and preventing a wound infection (23). Silver alginate dressings in particular are known to have prolonged antimicrobial efficacy, sometimes as long as 21 days, indicating sustained availability of ionic silver and therefore the requirement of fewer dressings changes (24). Metallic silver is inert, but will release silver ions in an aqueous environment.…”
Section: Introductionmentioning
confidence: 99%